1997
DOI: 10.1089/cbr.1997.12.277
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Anthocyanin Fractions Extracted from Red Soybeans and Red Beans in vitro and in vivo

Abstract: Many bioflavonoids extracted from petals of higher plants and from fruit rinds, as well as purified flavonoids, have been reported to have antitumor effects in vitro and in vivo. Bioflavonoids extracted from red soybeans are mostly cyanin conjugated with glucose and rhamnose, whereas bioflavonoids of red beans are cyanin conjugated with rhamnose as revealed by thin-layer chromatogram. Flavonoids extracted from red soybeans were effective in inhibiting the growth of HCT-15 cells in vitro. On the other hand, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 4 publications
3
41
0
6
Order By: Relevance
“…Such inhibitory influence was also expected from earlier investigations, in which juice or extracts of plants containing large amounts of anthocyanins acted as inhibitors of heterocyclic amine mutagenesis (Edenharder et al, 1994;Edenharder et al, 1995;Yoshimoto et al, 1999). Furthermore, anthocyanins have been reported to show anticancer activity (Bomser et al, 1996;Koide et al, 1997Koide et al, , 1996. As the PhIP intakes of rats fed PhIP plus PSPC or RCC were higher than that of rats given PhIP alone, the inhibitory effect of PSPC or RCC was not due to altered carcinogen exposure.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Such inhibitory influence was also expected from earlier investigations, in which juice or extracts of plants containing large amounts of anthocyanins acted as inhibitors of heterocyclic amine mutagenesis (Edenharder et al, 1994;Edenharder et al, 1995;Yoshimoto et al, 1999). Furthermore, anthocyanins have been reported to show anticancer activity (Bomser et al, 1996;Koide et al, 1997Koide et al, , 1996. As the PhIP intakes of rats fed PhIP plus PSPC or RCC were higher than that of rats given PhIP alone, the inhibitory effect of PSPC or RCC was not due to altered carcinogen exposure.…”
Section: Discussionsupporting
confidence: 70%
“…It is generally accepted that such anthocyanin food colors do not exert any toxicity, teratogenicity, or mutagenicity (Sano et al, 1996;Shimizu and Nakamura, 1993), and indeed anthocyanins may inhibit mutagenesis by environmental carcinogenic heterocyclic amines in the Ames test (Edenharder et al, 1994;Edenharder et al, 1995;Yoshimoto et al, 1999). Furthermore, it has been demonstrated that anthocyanins can act as antitumor agents in vivo and in vitro (Bomser et al, 1996;Koide et al, 1997;Koide et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are widely used as natural food colorants, and have been reported to have functional effects, such as antioxidant (Tsuda et al, 1998;Noda et al, 1998) antitumor (Koide et al, 1996;Koide et al, 1997), antimutagenicity (Yoshimoto et al, 1999), and others (Tsuda et al, 1999); they are also expected to be functional food ingredients. Research on production of secondary plant metabolites by plant cell and tissue cultures is increasing to find an effective system, or as one aspect of food biotechnology (Koda et al, 1992;Koda et al, 1993;Nawa & Ohtani, 1992).…”
mentioning
confidence: 99%
“…Anthocyanins in food have been linked with healthpromoting benefits such as antioxidant and anticancer activities (Koide et al 1997, Rechkemmer 2000. Seymour et al (2008) reported that eating of sour cherries reduced the lipid concentration of liver in animal experiment.…”
Section: Physiological Effect Of Flavonoidsmentioning
confidence: 99%